Oxygen Uptake and Heart Rate On-Kinetics during Prehabilitation in Patients with Scheduled Non-Small Cell Lung Cancer Resection - Gravier, Francis-Edouard; Buekers, Joren; Smondack, Pauline; Boujibar, Fairuz; Prieur, Guillaume; Medrinal, Clément; Combret, Yann; Muir, Jean-François; Baste, Jean-Marc; Cuvelier, Antoine; Debeaumont, David; Bonnevie, Tristan (Respiration, 2023)
Background: Oxygen uptake (V̇O 2 ) and heart rate (HR) kinetics during a constant work-rate test (CWRT) are used to evaluate the response to exercise in healthy subjects as well as subjects with various pathologies. Objectives: This study aimed to explore the feasibility of these measures and their responsiveness to a prehabilitation program in patients with non-small cell lung cancer (NSCLC). Method: This study is preregistered (NCT04041297) ancillary analysis of a subgroup of individuals with NSCLC included in the Preo-Dens study (NCT03936764). Thirty individuals performed a moderate-CWRT before and after a 15-session prehabilitation program between July 2019 and April 2021. V̇O 2 and HR on-kinetics were extracted from the first 240 s of breath-by-breath data using Box-Jenkins transfer functions. Results: Pre/post V̇O 2 on-kinetic feature values were reliable for 25/30 participants, and pre/post HR kinetic feature values were reliable for 19/30. V̇O 2 time constant (τ) and mean response time reduced from pre-post prehabilitation (mean difference −7.8 s; 95% CI: −14.6 to −1.0, and −8.4 s; 95% CI: −14.7 to −2.0, respectively). For HR on-kinetics, τ did not change from pre-post prehabilitation (median difference −4.0 s; 95% CI: −36.0 to +11.0). V̇O 2 and HR response amplitudes reduced significatively from pre-post prehabilitation (mean difference −38.6 mL/min; 95% CI: −73.3 to −3.9, and −3.1 beats/min; 95% CI: −6.4 to −0.2, respectively). Conclusion: V̇O 2 on-kinetic analysis during moderate-CWRT is feasible in individuals with scheduled NSCLC resection, and results are responsive to prehabilitation. These results support a true speeding of the adaptation of aerobic metabolism after a 15-session prehabilitation program.